The purine salvage enzyme hypoxanthine guanine xanthine phosphoribosyl transferase is a major target antigen for cell-mediated immunity to malaria - Makobongo, Morris O. (The National Academy of Sciences, 2003)
Although there is good evidence that immunity to the blood stages of malaria parasites can be mediated by different effector components of the adaptive immune system, target antigens for a principal component, effector CD4(+) T cells, have never been defined. We generated CD4(+) T cell lines to fractions of native antigens from the blood stages of the rodent parasite, Plasmodium yoelii, and identified fraction-specific T cells that had a Th1 phenotype (producing IL-2, IFN-γ, and tumor necrosis factor-α, but not IL-4, after antigenic stimulation). These T cells could inhibit parasite growth in recipient severe combined immunodeficient mice. N-terminal sequencing of the fraction showed identity with hypoxanthine guanine xanthine phosphoribosyl transferase (HGXPRT). Recombinant HGXPRT from the human malaria parasite, Plasmodium falciparum, activated the T cells in vitro, and immunization of normal mice with recombinant HGXPRT reduced parasite growth rates in all mice after challenge.